Synthesis of Resorcin[4]arenes Using Microwave Irradiation and Conventional Heating - Mobinikhaledi, A.; Kalhor, M.; R. Ghorbani, A.; Fathinejad, H. (Asian Journal of Chemistry, 2010)
Resorcin[4]arenes (3a-h) were synthesized by reacting of an aromatic or aliphatic aldehyde, resorcinol, hydrochloric acid and methanol using both microwave irradiation and conventional heating methods in good yields. It has been found that synthesis of resorcin[4]arenes using microwave irradiation, comparative to conventional heating method is more convenient and easily controlled.